New Directions of China’s Economic Expansion in Africa (The Case of Equatorial Guinea) - DEYCH Tatiana Lazarevna (Ученые записки Института Африки Российской академии наук)
The article analyzes China’s cooperation with the Republic of Equatorial Guinea (REG). This country is out of the limelight of attention of scholars and media. Meanwhile, it is one of the leading oil producers in sub-Saharan Africa. Exploitation of oil and gas deposits, beginning in the 1990s, has driven economic growth in Equatorial Guinea. Declining revenue from hydrocarbon production, high levels of infrastructure expenditures, lack of economic diversification, and corruption have pushed the economy into decline in recent years and precluded the improvement in the general population’s living conditions from 2010 to 2014. Country experienced the reduction of foreign financial assistance. In the light of the economic difficulties in the country, as well as in the context of the national economic development plan “Horizons 2020” implemented by the government of Equatorial Guinea, which stipulates the need in investment, the Chinese assistance is of particular importance for REG. The author analyzes China-Equatorial Guinea trade relations and shows that Beijing has become the first partner of REG on export and the second – on import and the largest destination for REG oil exports. The article deals with Beijing’s activities as donor and investor in this African country. China has been increasing its presence in Equatorial Guinea, cooperating with this country in pressing issues such as infrastructure development. REG government seeks to diversify its economy. The government’s “Horizon 2020” initiative tries to build up infrastructure, particularly in the fields of healthcare, water systems, and transportation networks. The Chinese have been engaged in such projects. The article shows that China, which has established a strategic partnership with REG, plays an important role not only in the oil sector of the country, but also in its economy as a whole. The analysis of the problem leads to the conclusion that China makes a significant contribution to the implementation of the REG development plan.